Women’s empowerment and gender equality in South Asian agriculture: Measuring progress using the project-level Women’s Empowerment in Agriculture Index (pro-WEAI) in Bangladesh and India - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Malapit, Hazel J. (Elsevier, 2022)
This introduction to a special section describes how a recently developed measure, the project-level Women’s Empowerment in Agriculture Index (pro-WEAI) can be used to assess empowerment impacts of agricultural development interventions in India and Bangladesh as well as broader changes in rural labor markets. The special section comprises three papers. The first examines the impact of membership in self-help groups in five states in rural India on women’s and men’s empowerment and gender equality. The second presents experimental evidence from a pilot project in Bangladesh that provided trainings in agricultural extension, nutrition behavior change communication, and gender sensitization to husbands and wives together. The third investigates changes in women’s roles within the jute value chain in the Southern Delta region of Bangladesh as household members migrate out of the study area and the availability of male labor declines. Although these papers focus on Bangladesh and India, pro-WEAI can be applied to impact assessments of agricultural development projects more generally. The three papers show both the usefulness of this new measure in detecting changes in empowerment indicators within the lifespan of a project and the value of having explicit empowerment objectives in agricultural development projects. The papers also demonstrate the value of having data on both men and women so that project designers can be more intentional about including both of them and monitoring outcomes for both to promote more gender equitable outcomes.